Evaluation of the root canal cross-sectional morphology in maxillary and mandibular premolars in Saudi subpopulation - Nezar Mohammed Boreak; Mohammed Nasir Kamaluddin Inamdar; Sheeba Khan; Khalid A Merdad; Ahmad Jabali; Nassreen Albar; Hamed Alshawkani (Wolters Kluwer Medknow Publications, 2022)
Introduction: Cone-beam computed tomography (CBCT) is a recent advancement in diagnostic radiology in dentistry which allows the clinician to have a clear 3D view of the root canals before starting the endodontic treatment. The goal of the present research was to assess the root canal cross-sectional shape (RCCSS) in maxillary and mandibular premolars in the Saudi Arabian subpopulation. Materials and Methods: In the present study, radiographs of 330 patients who had teeth with complete root development and closed apices were selected. Root canal shapes were assessed at the coronal and middle thirds, and in the apical third, 1 mm above the apical foramen using CBCT. Categorical variables were explained as frequencies and percentages and evaluated using the Chi-square test. Results: 1666 premolars were evaluated in the study. Maxillary first and second premolars were found to have a maximum circular cross-sectional shape at the coronal, middle, and apical sections in most of them followed by flattened and oval cross-sectional shapes except the maxillary right second premolars where the most frequent RCCSS was flattened in the coronal section (71%), circular in the middle (14%), and apical (10%) section. The most recurring coronal RCCSS in mandibular first and second premolars was oval followed by flattened and circular, while the most frequent cross-sectional shape in the middle and apical sections was found to be circular followed by oval and flattened RCCSS. Conclusion: Marked variations were observed in the coronal and middle RCCSS of maxillary and mandibular premolars though the most prominent RCCSS in the apical section was the circular shape.